Standard Operating Protocol: Operating on COVID-19 patients - Thapa, Amit; Sharma, Krishna; Shrestha, Prabin (Nepal Journal of Neuroscience, 2020)
Due to lack of scientific evidence, guidelines cannot be formulated. Hence this protocol would serve as STANDARD OPERATING PROCEDURE (SOP) for performing neurosurgical procedures on COVID-19 suspect, probable or positive cases. This SOP is based on recommendations from various societies and experiences of the hospitals involved in care of patients with COVID-19. As the status of COVID-19 in Nepal change along with refinement in knowledge of the disease and its management, SOP would be updated. Objective is to “Serve with caution”. Nepal is presently in phase 2 of Global COVID-19 p The doubling time for active infections is shortening over the last two weeks (Figure 1). The healthcare facilities have to gear up and prepare to face the worst with the most efficient use of available resources. Neurosurgical emergencies may arise in COVID-19 patients (suspect or probable or positive) who are being managed in isolated wards or ICU. Such patients cannot be operated in routine operating rooms nor kept in routine ICU, as they pose threat of transmission of infection to other patients and health care workers (HCW). COVID-19 patients undergoing aerosol generating procedures (AGPs) pose higher risk of transmission of the SARS-CoV-2 virus. Special isolation precautions should be adopted by all health care workers (HCW) with specific protocols to stay safe as well as manage the case efficiently.